2017
DOI: 10.1103/physrevlett.118.096401
|View full text |Cite
|
Sign up to set email alerts
|

Dirac Fermions in Borophene

Abstract: Honeycomb structures of group IV elements can host massless Dirac fermions with non-trivial Berry phases. Their potential for electronic applications has attracted great interest and spurred a broad search for new Dirac materials especially in monolayer structures. We present a detailed investigation of the β12 boron sheet, which is a borophene structure that can form spontaneously on a Ag(111) surface. Our tight-binding analysis revealed that the lattice of the β12-sheet could be decomposed into two triangula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
372
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(402 citation statements)
references
References 46 publications
(48 reference statements)
13
372
4
Order By: Relevance
“…The conduction and valence bands in graphene touch with linear dispersion at discrete Dirac points on the Fermi level, around which the low-energy electrons behave like relativistic massless Dirac fermions in 2D, exhibiting properties distinct from the usual Schrödinger fermions. Inspired by graphene, much effort has been devoted to the search for other 2D materials which host Dirac/Weyl points, and a number of candidates have been proposed 3 , such as silicene 4,5 , germanene 4,6 , graphyne 7 , 2D carbon and boron allotropes [8][9][10][11][12] , group-VA phosphorene structures 13,14 , and 5d transition metal trichloride 15 . The Dirac points in all these materials (including graphene) are protected by symmetry, but only in the absence of spin-orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…The conduction and valence bands in graphene touch with linear dispersion at discrete Dirac points on the Fermi level, around which the low-energy electrons behave like relativistic massless Dirac fermions in 2D, exhibiting properties distinct from the usual Schrödinger fermions. Inspired by graphene, much effort has been devoted to the search for other 2D materials which host Dirac/Weyl points, and a number of candidates have been proposed 3 , such as silicene 4,5 , germanene 4,6 , graphyne 7 , 2D carbon and boron allotropes [8][9][10][11][12] , group-VA phosphorene structures 13,14 , and 5d transition metal trichloride 15 . The Dirac points in all these materials (including graphene) are protected by symmetry, but only in the absence of spin-orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of having such topological states has triggered an enormous amount of interest in searching for new materials with Dirac dispersion. Among recent proposals for 2D Dirac materials such as borophene 3 , stanene 4 , and silicene 5 , the 2D semi-Dirac (SD) systems 6 seem to have many exotic and unusual properties 7,8 due to their anisotropic band dispersion: linear in one direction and parabolic along the perpendicular direction. Promising candidates for such semi-Dirac systems include TiO 2 /V 2 O 3 layered structures 9 , deformed graphene 10 , BEDT-TTF 2 I 3 salt under pressure 11 , hexagonal and square lattices in the presence of magnetic field 12,13 , photonic systems 14 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a bigger nontrivial SOC gap in their Dirac cone is induced. [49][50][51] Besides, theoretical studies also indicated that borophene might possess Dirac Fermions [52] and exhibit superconductivity [53] at low temperatures. For example, it was reported that a nontrivial SOC gap of intrinsic stanene was over 30 meV.…”
Section: Current Status Of 2d Materials Researchmentioning
confidence: 99%